OPTIMIZING KNOWLEDGE ON THE PREVENTION OF SEXUAL VIOLENCE IN ELEMENTARY SCHOOL CHILDREN THROUGH ANIMATION VIDEO-BASED EDUCATION - Maria Anita Yusiana; Sutik (Suluh Adiluhung Publisher (SAPub), 2026)
This Community Service activity aims to increase students' knowledge about primary prevention of sexual violence through sexual education using animated video media at SDN Singonegaran 2 Kediri City. The program is carried out based on the needs of partners for health education that is in accordance with the characteristics of elementary school age children so that material on sexuality, forms of sexual harassment, the impact of sexual violence, and self-protection efforts can be delivered in an attractive and easy-to-understand manner. The implementation method includes health counseling using animated video media followed by interactive discussions and evaluations using pre-test and post-test designs for 18 students as participants in the activity. The results of the activity showed that before education, most participants had a level of knowledge in the sufficient category as many as 9 respondents (50.0%), the poor category as many as 7 respondents (39.0%), and the good category as many as 2 respondents (11.0%). After the implementation of education, the majority of participants were in the good knowledge category as many as 12 respondents (67.0%), while the sufficient category was 4 respondents (22.0%) and the poor category was 2 respondents (11.0%). The analysis of the evaluation results showed that there was a significant difference between the level of knowledge before and after the implementation of education. In addition to improving the results of knowledge measurement, the output of the activity showed that participants were able to recognize forms of sexual violence, understand its impact, and know the steps that must be taken if they face situations that endanger them. Thus, sexual education through animated video media is effective in increasing students' knowledge about primary prevention of sexual violence and can be used as a health education medium that supports promotive and preventive efforts in the elementary school environment.